Effect of integrated nutrient management on sequential productivity, economics and nutrient uptake of rice (Oryza sativa) - potato (Solanum tuberosum) cropping sequence - ROY, RINA; SINGH, KALYAN (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted at Banaras Hindu University, Varanasi, Uttar Pradesh during 2010-12 to evaluate the effect of nine different combinations of integrated plant nutrient supply including 3 different type of composts prepared from carpet waste generated in huge amount from carpet industry, farmyard manure and compared with the recommended dose of NPK (120:60:60 kg/ha) through inorganic fertilizer on productivity, economics, energetic, nutrient uptake and soil health of rice (Oryza sativa L.) - potato (Solanum tuberosum L.) cropping sequence. Bioinoculants such as cellulose decomposers (Trichoderma viride, Pleurotus sajor), P-solubilizing microbes (Bacillus polymyxa) and free living N-fixers (Azotobacter spp), essential nutrients, i.e. S and Zn were used as compost culture to hasten the composting process and improve the quality of the composts. The results indicated that net energy return (260 033.2 Rupees/ha), rice grain equivalent yield and nutrient uptake was significantly (P < 0.05) higher under recommended dose of NPK compared to the rest of the treatments but statistically similar with 75% RN through inorganic fertilizer and 25% N through carpet waste + cow dung slurry + Pleurotus sajor + Azotobacter + PSB + Trichoderma + enriched with S and Zn (251 886 Rupees/ha). The soil fertility status was found to be significantly improved due to application of various composts compared to sole application of 100% NPK inorganic fertilizer. Thus, substitution of chemical Nfertilizer to the tune of 25% nitrogen through carpet waste + cow dung slurry + Pleurotus sajor + Azotobacter + PSB + Trichoderma + Enrichment with S and Zn increased productivity and profitability in rice-potato cropping sequence with better soil health on long term basis.